Effects of density and dietary supplementation of fatty acids on growth and survivability of red swamp crayfish (Procambarus clarkii) - Karaban, Kamil; Stęplowski, Kacper (Studia Ecologiae et Bioethicae, 2018)
Red swamp crayfish (Procambarus clarkii) is an aquaculture and aquarium species. Due to its use in the food industry, any information on increasing survival and growth rate of juveniles is considered important. One hypothesis tested in our study involved competition for resources and risk of cannibalism in young individuals. We examined the impact of density on the growth rate and survival of juvenile crayfish in a laboratory experiment. The second hypothesis tested concerned the implementation of a crayfish diet with saturated (palmitic) and unsaturated (α-linolenic) fatty acids. α-Linolenic acid is considered a precursor to the production of EPA and DHA, which are a source of food and may be important for the condition of crayfish in the early stages of their growth and ultimately improve the quality of their muscles. Palmitic acid is one of the dominant fatty acids in the body of crayfish and, like α-linolenic acid, can be a source of food for crayfish. The mixed treatment with α-linolenic and palmitic fatty acids was aimed at determining whether crayfish will respond better to a varied diet than a diet dominated by one of the fatty acids. The experiment studied both hypotheses simultaneously, as planned for a two-way ANOVA analysis. Our results show that the density of crayfish and supplementation of fatty acids in their diet do not affect crayfish survivability but cause changes in the growth rate of individuals. Higher density stimulates crayfish to grow faster and reach larger sizes. The addition of palmitic or α-linolenic fatty acids in the diet causes faster growth. Interestingly, the alternating addition of these acids did not cause a significant effect.